STUDI SUBSTITUSI PEMANFAATAN ABU CANGKANG KEMIRI SEBAGAI PENAMBAHAN AGGREGAT HALUS TERHADAP KUAT TEKAN BETON Fc’ 14,53 MPa - Rahmad Ilham; Masril Masril; Ana Susanti Yusman (Ensiklopedia Research and Community Service Review, 2022)
Concrete is a mixture of portland cement or other hydraulic cement, coarse aggregate, fine aggregate and water, with or without additives that form a solid mass (SNI-03-2847-20020). This research is to find out the compressive strength of environmentally friendly concrete by utilizing the results of burning candlenut shells as a new alternative to obtain concrete obtained from waste bark. The method used is a quantitative method with research in the Civil Engineering laboratory of the University of Muhammadiyah, West Sumatra. The purpose of this study is to find out how much influence candlenut shell ash has as a partial replacement of fine aggregate on the compressive strength of concrete and to find out how much influence candlenut shell ash has as a partial replacement of fine aggregate with a percentage of 0%, 10%, 15%, and 20%. of the weight of the fine aggregate. Benefits of the research Provide knowledge on the use of candlenut shell ash as a partial replacement for fine aggregate in the manufacture of concrete. From the results of the study, it can be concluded that the mixture of concrete with hazelnut shell ash fc' 14.53 occurred at an additional 10% percentage at 28 days of concrete age, namely 8.87 MPa, 15% percentage at 28 days concrete age of 14.53 MPa, while in the percentage of 20% at the age of 28 days of concrete is 12.46 MPa.Keywords: 12,53 MPa quality of concrete , compressive strength, candlenut shell ash.